Management of Physical Education Facilities and Infrastructure - Dewi, Citra; Windoro, Desrio; Pura, Dwi Naomi (Universitas Pendidikan Ganesha, 2021)
Lack of facilities and infrastructure for physical education causes students to have difficulty exercising. Attention to physical education facilities and infrastructure have not been maximally achieved. Most schools do not consider planning, providing or procuring, using, and maintaining physical education facilities and infrastructure. This study aims to analyze the management of physical education facilities and infrastructure. This research is descriptive research with a qualitative approach. Qualitative research aims to understand social phenomena from the participant's perspective. These participants are interviewed, observed, asked to provide data, opinions, thoughts, and perceptions. The research strategy is flexible, using various combinations of techniques to obtain valid data through surveys. Based on the study results, it was found that interviews showed that: first, the planning of physical education learning facilities was carried out based on needs analysis and determining the priority scale of activities to be carried out, according to availability: funds and their importance. Second, the provision of learning facilities is carried out by prioritizing function (utility), which refers to the facility's usefulness—related to the real needs of the school. Third, the use of physical education learning facilities and academic activities in teaching and learning in the classroom is also used to support the implementation of various school activities. Fourth, the storage of learning facilities is coordinated by designated personnel—appointment of personnel on agreed terms.